2013
DOI: 10.1080/10888438.2011.624566
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Practice Reading Aloud: Ten Versus Twenty Minutes

Abstract: In this study we compared effects of practice time reading aloud to an adult on improvement in reading rate and comprehension. Eighty-one poor readers in 2nd and 4th grade, including 38 English Learner students (ELs), served as their own controls by participating in two practice conditions, each 3 times per week for 7 weeks: (a) 10 min reading aloud one-to-one to an adult listener and (b) 20 min reading aloud one-to-one. Repeated measures analysis of variance showed that 20 min of practice was better than 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 65 publications
3
11
0
Order By: Relevance
“…There is agreement that fluent reading depends on well‐established orthographic representations and that these representations are influenced by reading practice (for review, see Cunningham, Nathan, and Raher, ). The current study adds to several strands of previous research that supports a role for sublexical orthographic representations in fluency development (see also, O'Connor et al, ). These strands of previous research include: i) short‐term studies that suggest a connection between training sublexical units and reading words with those units (e.g., Hintikka et al, ); ii) studies that show a relationship between sublexical automaticity defined as speed at individual grapheme‐phoneme correspondences and/or phonogram speed and oral‐reading fluency (Hudson et al, ; Speece and Ritchey, ); and iii) multidimensional interventions that include teaching sublexical units and show improvement in standardized reading fluency scores (e.g., Morris et al, ).…”
Section: Discussionsupporting
confidence: 68%
“…There is agreement that fluent reading depends on well‐established orthographic representations and that these representations are influenced by reading practice (for review, see Cunningham, Nathan, and Raher, ). The current study adds to several strands of previous research that supports a role for sublexical orthographic representations in fluency development (see also, O'Connor et al, ). These strands of previous research include: i) short‐term studies that suggest a connection between training sublexical units and reading words with those units (e.g., Hintikka et al, ); ii) studies that show a relationship between sublexical automaticity defined as speed at individual grapheme‐phoneme correspondences and/or phonogram speed and oral‐reading fluency (Hudson et al, ; Speece and Ritchey, ); and iii) multidimensional interventions that include teaching sublexical units and show improvement in standardized reading fluency scores (e.g., Morris et al, ).…”
Section: Discussionsupporting
confidence: 68%
“…These results are consistent with parallel research topics. For instance, a meta-analysis regarding the effectiveness of online and blended learning, conducted by Means et al (2013), indicated that the social context was a moderator variable of the online and blended learning effect size. Another meta-analysis regarding the effectiveness of flipped classroom instruction, conducted by Shi et al (2019), also indicated that the social context was a moderator variable of the flipped classroom instructional effect size.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive learning is a clear indicator for evaluating the quality of education (Michaelowa, 2010), and it is commonly measured either through examinations or through continuous assessments. Inspired by the framework proposed by Means, Toyama, Murphy, and Baki (2013) and a review of the moderator variables included in other recent meta-analyses (Hew & Lo, 2018;Shi, Ma, MacLeod, & Yang, 2019), the conceptual framework for this study was guided both by data extraction of the studies included in the meta-analysis and a follow-up moderator analysis, as shown in Figure 1. The framework comprises three categories: (a) instructional experiences of TE-ALEs, including social context, information and communication technology (ICT) features, and treatment duration; (b) the conditions of the studies, including the year of publication and subject matter; and (c) features of the research methodology, including study design, sample size, and instructor equivalence.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations